The role of interpersonal coordination dynamics in alliance rupture and repair processes in psychotherapy—A systematic review - Høgenhaug, S. S.; Kongerslev, M. T.; Kjaersdam Telléus, G. (Frontiers in Psychology, 2024)
Introduction The purpose of this systematic review is to expand our knowledge of the underlying mechanisms of the alliance in psychotherapy. This is done by examining the association between alliance rupture and repair processes and interpersonal coordination dynamics. Method A systematic review based on PRISMA guidelines was conducted, aimed at papers investigating the association between alliance rupture and repair episodes and different behavioral modalities (i.e., physiology, movement) in the psychotherapeutic interaction. Seventeen studies were included for full text-analysis. Results The results indicate that rupture and repair episodes were associated with interpersonal coordination dynamics. Different modalities (movement, heart rate, and vocalization) were found to serve as markers for alliance rupture and repair events. Facial expressions, physiological arousal, vocalization, and behavior were found to play important roles in the therapeutic interaction in relation to mutual emotion regulation, empathic response, safety, trust, and meaning-making. Discussion Limitations of this review are discussed, including the great methodological variation and selection bias observed in the reviewed studies. Recommendations for future research in this area are presented. Overall, interpersonal coordination dynamics was found to have the potential to help identify and manage alliance ruptures and foster repairs in the therapeutic interaction, which has high potential for future clinical work and training.